Li2O-B2O3-Li2SO4 modified LiNi1/3Co1/3Mn1/3O2 cathode material for enhanced electrochemical performance. (1st September 2017) - Lv, Dingding; Wang, Lei; Hu, Pengfei; Sun, Zhipeng; Chen, Zhaoyang; Zhang, Qibing; Cheng, Wenhua; Ren, Wei; Bian, Liang; Xu, Jinbao; Chang, Aimin
Highlights: Li2 O-B2 O3 -Li2 SO4 is used as a coating material in the cathode. Surface modification enhances rate capability of LiNi1/3 Co1/3 Mn1/3 O2 sample. At −20 °C, modified LiNi1/3 Co1/3 Mn1/3 O2 samples deliver a high discharge capacity. Modification via Li2 O-B2 O3 -Li2 SO4 increases ionic conductivities. Abstract: A poor performance of the ternary cathode material, LiNi1/3 Co1/3 Mn1/3 O2, at rate capability and low temperature, limits its further application, in electronic markets. Some of the previous research works report that surface modification of cathode materials can enhance their cycle stability. In the current work, (42.5-x) Li2 O: 57.5B2 O3 : xLi2 SO4 modified LiNi1/3 Co1/3 Mn1/3 O2 cathode materials are prepared via the solution method followed by heat-treatment at 500 °C. The lithium fast ion conductors (42.5-x) Li2 O: 57.5B2 O3 : xLi2 SO4 provide a stable surface protection for LiNi1/3 Co1/3 Mn1/3 O2 . The results indicate that (42.5-x) Li2 O: 57.5B2 O3 : xLi2 SO4 modified LiNi1/3 Co1/3 Mn1/3 O2 exhibits enhanced electrochemical performance at high rates and low temperatures. (42.5-x) Li2 O: 57.5B2 O3 : xLi2 SO4 (x = 10) modified LiNi1/3 Co1/3 Mn1/3 O2 samples increase the discharge capacity retention of LiNi1/3 Co1/3 Mn1/3 O2 from 33.4% to 85.3% at the rate of 1C and from 48.6% to 70.0% at −20 °C. The high resolution transmission electron microscopy and scanning electron microscopy confirm the existence of a thin Li2 O-B2 O3 -Li2 SO4 coating layer (about 10 nm) on the original structure of LiNi1/3 Co1/3 Mn1/3 O2 . The cyclic voltammetry and electrochemical impedance spectroscopy test results demonstrate that the presence of LBO-S coating reduces the interfacial resistance towards lithium ion migration.